CHALLENGES CONFRONTING NIGERIA INDIGENOUS CONSTRUCTION ENTERPRISES - Akinsiku, Olusegun Emmanuel (Journal of Surveying, Construction and Property, 2020)
Construction activities in Nigeria are dominated by foreigners’ managed construction enterprises. These companies constitute less than 5 percent of the number of construction enterprises in Nigeria; however, they are involved in over 95 percent of high net-worth construction activities. Nigeria Indigenous Construction Enterprises (NICE) are faced with numerous challenges that have limited their performances. This makes construction clients to patronize foreigners’ managed construction firms because of the flaws in the performances of NICE. There have been measures on how to make NICE relevant, but most attempts have achieved little or no success. This study was aimed at examining the challenges of NICE in the face of the present scenario and to proffer ways of possible improvement. Primary data were collected by administering a structured questionnaire to both clients and contractors who are involved in the day-to-day construction activities. Data collected were analyzed using descriptive statistics, mean score and Kruskal-Wallis test. The study identified 25 challenges of NICE and 18 ways of improving NICE performance through careful literature reviews. The analysis of the total ranking among stakeholders revealed that limited technical expertise, insufficient profit on projects and delay in the payment of contractors for work done were the highest-ranked challenges. Application of project management techniques in construction activities, quality control of materials and improving production capabilities were the most important means of improving NICE performance as identified. The findings of this study will help to improve the competitiveness of indigenous contractors if well implemented as it will help to reduce the cost of construction as the competition nest for performing contractors will be widened.